Neutron-rich clustering investigation at LNS with FARCOS detectors - Risitano Fabio; Gnoffo Brunilde; Trimarchi Marina; Acosta Luis; Cardella Giuseppe; De Filippo Enrico; Dell’Aquila Daniele; Geraci Elena; Lombardo Ivano; Maiolino Concetta; Martorana Nunzia Simona; Pagano Angelo; et al. (EPJ Web of Conferences)
The physics of clusters in heavy neutron-rich ions is a topic of constant interest in the worldwide scientific community. In recent times, many interesting phenomena have been investigated especially thanks to the development of new radioactive beam production facilities. One example is the clustering of α particles in neutron-rich isotopes of self-conjugated nuclei, such as 10Be or 16C, exhibiting even very large nuclear deformations. At Laboratori Nazionali del Sud of INFN, a study was carried out on the topic of α clustering, employing the CHIMERA and FARCOS detectors. Radioactive ions of interest, such as 10Be, 13B and 16C, were produced in a cocktail beam through the In-Flight fragmentation technique by the FRIBs@LNS facility. Particularly important for this study was the employment of four FARCOS detectors, offering high angular and energetic resolutions. Several calibration and analysis techniques have been exploited and developed in this experiment for the analysis of the data collected by FARCOS. Finally, some preliminary results on the analysis of 10Be and 16C spectroscopy will be shown, in relation to some results already collected in the literature.